Problems of sexual violence as a human rights violation in the context of armed conflicts - Svitlana, Karvatska (Національний університет "Одеська юридична академія", 2023)
The article analyzes sexual violence as a violation of human rights. It is argued that during an armed conflict, cases of such violence can be interpreted as crimes against humanity, war crimes, or genocide. Violence against women, especially sexual violence, has been used during armed conflicts throughout human history. ¥exual violence is only one of many forms of violence in armed conflict. They can be paired with mass killings, displacement of civilians, arbitrary detention, abductions, looting, and massive destruction of civilian property and critical infrastructure as a form of violence. The risk of violence, including sexual violence, is higher in certain cases and under certain conditions, such as in detention. It is crucial to emphasize the absence of various legal and organizational mechanisms (procedures) that ensure social and legal protection of a person, functioning to provide the most favorable conditions for the realization of the constitutionally enshrined human status in armed conflict. In this regard, it makes sense to pay attention to international legal acts regulating the situation of women during military conflicts. It is proved that at the moment, Ukraine lacks the necessary effective and comprehensive mechanisms for documenting and recording crimes of sexual violence related to the armed aggressive war of the 6ussian Tederation against Ukraine. In addition, employees of competent law enforcement and prosecutor's offices are not always familiar with the principles and standards of working with victims of such crimes. In conclusion, it is stated that it appears necessary for the relevant authorities of Ukraine to ensure the systematic collection of information on cases of sexual violence.
Keywords: human rights, crimes against humanity, armed conflict, women's rights, sexual violence